Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 4 - Applications of the Derivative - 4.9 Antiderivatives - 4.9 Exercises - Page 327: 9

Answer

$$C = 0$$

Work Step by Step

$$\eqalign{ & F\left( x \right) = {x^2} - 3x + C,{\text{ we know that }}F\left( { - 1} \right) = 4,{\text{ then}} \cr & 4 = {\left( { - 1} \right)^2} - 3\left( { - 1} \right) + C \cr & 4 = 1 + 3 + C \cr & 4 = 4 + C \cr & C = 0 \cr} $$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.